The spatiotemporal evolution of a giant submarine canyon system – the Agadir Canyon - Böttner, Christoph; Stevenson, Christopher J.; Geersen, Jacob; Krastel, Sebastian (Frontiers in Earth Science, 2025)
Submarine canyon systems are gateways for sediment transport from the shelf to the deep sea. They are the primary conduit for gravity flows that move substantial amounts of carbon, nutrients, and pollutants from the continental shelves to the deep sea. Despite their importance, it often remains unclear how these canyons initiate, and which factors determine their evolution from initiation to mature stage. The Agadir Canyon, located at the Northwest African Continental Margin, represents one of the largest canyon systems worldwide and a conduit for some of the largest turbidity currents on Earth. However, our understanding currently rests on legacy DSDP drilling and poorly resolved seismic imaging of turbidites beyond the canyon mouth. Here, we present multichannel seismic data from proximal and distal reaches of the Agadir Canyon combined with age constraints from the DSDP borehole. This allows us to detail its morphological and temporal evolution from inception to present-day. The Agadir Canyon initiated during the Middle Miocene on top of a preceding wide and shallow channel-levee-system. The Middle to Late Miocene saw the canyon continue eroding and narrowing into its present morphology. The evolution of the canyon was primarily driven by climate perturbations, sea level fluctuations and regional tectonic uplift of the Moroccan hinterland. These factors increased sandy sediment supply to the shelf edge, which promoted powerful erosive turbidity currents. However, most of the canyon fill is slope-derived mud-rich mass transport deposits, which healed the canyon morphology over geologic timescales. Regional salt diapirism, the development of the Canary Islands and the onset of bottom currents during the Miocene actively re-routed sediments and actively shaped its morphology. These competing processes produced the distinct giant canyon morphology seen today: deeply incised (up to 1.2 km) with a flat-bottomed and wide floor (up to 30 km across) that extends for ∼400 km down slope.